The break with the past : avant-garde architecture in Germany, 1910-1925 - Barnstone, Deborah Ascher (2018)
Between 1918 and 1933 the German interwar avant-garde was a primary force driving European cultural innovation and modernism. These innovations continue to influence artistic practice, theory, and arts education today, thus making a comprehensive study of the relationship between individual war experience and the immediate response of avant-garde architects after the war all the more important. The Break with the Past pursues several important, interrelated questions. What were the disparate war experiences of German architects and did they have different effects on Weimar cultural production? Did political orientation play a part in support for the war? In aesthetic choices? What changes occurred in avant-garde architectural practice after 1918? How do they compare with pre-war positions and practices and expectations for post-war outcomes? In order to address these questions, the book uses individual case studies of four leading architects, Bruno Taut, Walter Gropius, Erich Mendelsohn, and Hans Scharoun.